ANALISIS SEMIOTIKA KOMUNIKASI VIRTUAL PLAYER GAME DOTA 2 DALAM MENERAPKAN STRATEGI PSYWAR - Andreyano, Dimas; ", Suyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
DotA 2 game is one of the online game played by millions of people around the world. That vast scale led to the birth of huge online community so that the only way for them to communicate with each other is through virtual communication. Dota 2 players assume that winning the game is their priority so that they will do various way to be win, one of those is by applying psywar strategy that means war by words through the chat and interaction through the web. This study aimed to fiind out the meaning dennotative, connotative, and myth then how it applies in psywar strategy of DotA 2. This study methods is Roland Barthes semiotics analysis which consist of the meaning of dennotation, connotation, and myth. Data collected by used documentation study, observation study, literatur study, online data searching, and interview. The object being analyzed is the screenshoots in DotA 2 game as much as 5 unit analysist. The results showed that there are three meanings according to Roland Barthes semiotics. The meaning of denotation is the words conveyed by the players by using the English phrase, The meaning of connotation is a hidden meaning and not in accordance with the meaning of chat that the players delivered literally, while the myth is a habit of DotA 2 players around the world that result in conventions through Their experiences during the game DotA 2. Psywar strategy implementation is done by instigating, insulting opposing players, and pretending to surrender or known as fake GG.Keywords: semiotic, game, DotA 2